Standardising Maritime English Training And Assessment through International Coordination of Content-Based Instruction - Annamaria Gabrielli (Scripta Manent)
The current provisions of the International Maritime Organization (IMO) Standards of Training, Certification and Watchkeeping (STCW Manila; IMO, 2010) for language proficiency and communication skills require standard levels for cadets’ communication skills worldwide, but do not suggest how to coordinate standardised Maritime English (ME) training and assessment across the globe in order to consistently meet these requirements. The responsibility for globally standardised assessment of cadet ME skills at Maritime Education and Training (MET) institutions around the world is therefore shouldered by the trainers only. This inevitably leads to differences in local interpretations of the ME standards. The central interest of the International Maritime Lecturers Association (IMLA) and the International Maritime English Conference (IMEC) is therefore to develop consistent assessment methods for cadets’ ME skills, which can be implemented worldwide. This paper explores current ME training practice worldwide, and suggests cross-curricular, content-based instruction as a solution for globally unified and coordinated standards of ME skills assessment.